Analysis of Factors Causing Delays in Coal Loading on the MV TAI SPRING Due to Fire in the Cargo - Suryadi, Awel; Hidayat, Syaefulah; Prasetiawan, Andi; Kurniawan, Iwan (Politeknik Ilmu Pelayaran Semarang, 2025)
Coal cargo fire during the loading process is very dangerous and detrimental to various parties involved. In Indonesia, one of the incidents of coal cargo fire occurred during the loading process of MV TAI SPRING located in Muara Jawa, Kutai Kartanegara, East Kalimantan, causing delays in scheduled loading and causing losses to several parties involved. The research was conducted using a descriptive qualitative method with primary and secondary data collection through observation, interviews, documentation, and literature studies. Data analysis used the Miles and Huberman technique, then supplemented with the Fishbone technique and data validity by triangulation. The results of the study showed that the fire in the cargo was caused by the cargo owner who during loading on the MV TAI SPRING had not implemented periodic cargo temperature checks, environmental conditions that had weather according to tropical conditions were balanced by open coal loading conditions that allowed the cargo to be exposed to direct sunlight. The impact of loading delays due to fires in the cargo includes delays in the loading process due to efforts to extinguish the fire, additional costs to the PBM, delays in processing administrative documents due to late loading, and additional logistics costs for large vessels. Therefore, efforts to extinguish fires in the cargo are necessary by using a bulldozer to cool down the cargo.